2020
DOI: 10.1097/aud.0000000000000848
|View full text |Cite
|
Sign up to set email alerts
|

Age Affects Speech Understanding and Multitask Costs

Abstract: Objectives: We examined the effect of age on speech understanding and multitask costs in the ecologically relevant 'Audio-Visual True-to-Life Assessment of Auditory Rehabilitation'paradigm (AVATAR).Design: Twenty-nine normal hearing middle-aged adults completed AVATAR, which combines an auditory-visual speech-in-noise task with three secondary tasks on auditory localization or visual short-term memory in different dual-, triple-and quadruple-task combinations. Performance decrements on the secondary tasks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Noteworthy, differences in secondary task performance between participants might be more apparent under the SPIN+5dB condition compared to SPIN50%, given that performance on the main listening task is equalized under the SPIN50% condition. However, previous research showed that, even when speech understanding performance was equalized between participants, group differences in secondary task performance were still apparent (Devesse et al 2020b).…”
Section: The Cost Of Intrinsic and Extrinsic Cognitive Demands On Aud...mentioning
confidence: 96%
See 1 more Smart Citation
“…Noteworthy, differences in secondary task performance between participants might be more apparent under the SPIN+5dB condition compared to SPIN50%, given that performance on the main listening task is equalized under the SPIN50% condition. However, previous research showed that, even when speech understanding performance was equalized between participants, group differences in secondary task performance were still apparent (Devesse et al 2020b).…”
Section: The Cost Of Intrinsic and Extrinsic Cognitive Demands On Aud...mentioning
confidence: 96%
“…As a primary aim, we investigated the impact of intrinsic and extrinsic cognitive demands on auditory perception and multitask costs by means of a behavioral multitasking paradigm that mimicked auditory spatial complexity and visual (speech) cues, called 'Audio-Visual True-to-life Assessment of Auditory Rehabilitation' (AVATAR). AVATAR previously proved to be a promising ecologically relevant model to provide a full picture of auditory functioning, that is, to assess both auditory performance and the amount of processing resources during effortful listening (Devesse et al 2019;Devesse et al 2020). Second, we investigated whether older adults with NH differed from hearing impaired adults using hearing aids (HA) on auditory abilities and secondary task performance.…”
Section: Introductionmentioning
confidence: 99%
“…AVATAR was developed by Devesse and colleagues [1][2][3][4] to investigate the impact of multiple tasks on speech perception in noise (SPIN). It consists of a program which displays a computer-graphics environment with virtual human figures (see Fig.…”
Section: Avatarmentioning
confidence: 99%
“…The virtual humans can be made to animate their mouths realistically in synchrony with audio material being presented by a separate program. This paradigm has proven successful in eliciting audiovisual benefit [2]. In addition to the SPIN task, three other tasks can be added: a localization task, wherein a phone rings in one of the five possible speaker locations, and the participant is asked to indicate which direction the ringing had come from; a dynamic task, wherein the sound of a fly passing from left to right or from right to left is presented, and the participant is asked to indicate which direction it had gone; and a visual task, wherein participants were required to remember a number present on the scene and which changes between trials.…”
Section: Avatarmentioning
confidence: 99%
“…Results showed that LE increased initially in the fourth decade of life and was related to the cognitive attribute of speech recognition in degraded listening conditions. Devesse et al (2020) were among the few studies that focused specifically on participants in the age range of 45-60 years. The performance of 29 middle-aged adults was compared to that of 35 young adults in auditory-visual speech-in noise task that combined dual, triple, and quadruple secondary tasks, to approximate real life situations.…”
Section: Introductionmentioning
confidence: 99%